Emotional Reactivity Classification Using Artificial Intelligence Based on Twitter in Bahasa Indonesia - Paramita, Greta V.; Andangsari, Esther W.; Kemala, Ade P.; Ali, Moondore M.; Putri, Trisa M.; Puspita, Katarina I. (2023 IEEE 3rd International Conference on Social Sciences and Intelligence Management (SSIM), 2023)
Twitter is one of Indonesia's most widely used social media to express positive and negative emotions. Negative emotions are referred to as emotional reactivity, an example of which is depression. To detect emotional reactivity, Artificial Intelligence (AI) was used. With deep learning pretrained model methods (IndoBERT and IndoBERTweet), AI successfully classified emotional reactivity. AI satisfactorily detected emotional reactivity on Twitter.